THE INFLUENCE OF ACHIEVEMENT MOTIVATION AND SELF ESTEEM ON STUDENTS' ISLAMIC RELIGIOUS EDUCATION LEARNING OUTCOMES - Abdi, Hamdani; Zuhri, M; Suanti, Linda; Ridwan, Ridwan (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Achievement motivation and self-esteem are crucial psychological factors in determining students’ learning success, including in Islamic Religious Education (PAI). Purpose: This study aims to examine the influence of these two factors on PAI learning outcomes among students at SMP Negeri 39 Padang. Method: Employing a quantitative approach with multiple linear regression analysis, data were collected through questionnaires and final examination scores in PAI from 113 students. Result: The findings reveal that both achievement motivation and self-esteem have a positive and significant effect on PAI learning outcomes, with self-esteem emerging as the more dominant factor. Conclusion: These results highlight the essential role of teachers in fostering students’ self-esteem and achievement motivation through positive instructional strategies to enhance their academic achievement.